Efektivitas Regulasi dan Implementasi Hukum Terhadap Pertambangan Batubara Tanpa Izin di Indonesia - Dela Meilany (Program Studi Ilmu Hukum, Universitas Kuningan, 2024)
This research aims to identify the effectiveness of regulations and legal implementation regarding illegal coal mining in Indonesia, focusing on a case study of case No. 210/Pid.Sus/2024/PN Bta. Illegal coal mining (PETI) is a serious problem with negative environmental, social, and economic impacts in Indonesia. This research uses a normative method, namely the literature review principle, which involves collecting and reviewing several sources. Despite various regulations governing legal mining activities, illegal mining practices remain rampant. In this context, this study analyzes the extent to which existing regulations, such as Law No. 4 of 2009 concerning Mineral and Coal Mining and Government Regulation No. 23 of 2010, are implemented. Despite existing regulations, their implementation is hampered by factors such as inter-agency coordination, limited resources, and suboptimal community participation. Therefore, it is recommended to improve oversight, strengthen community participation, and implement policy reforms to improve the effectiveness of legal implementation regarding illegal coal mining in Indonesia.